Solar-floating Co–N4 single-atom catalyst platform for neutral-pH H2O2 generation and algal bloom mitigation - Oh, Cheoulwoo; Lee, Youngrok; Kim, Min Woo; Oh, Sangmin; Kim, Kibeom; Lee, Woong Hee; Park, Jong Hyeok; Choi, Shinwoo; Kim, Sunghyun; Kim, Nam Dong; Cho, Hyesung; Oh, Hyung-Suk (Elsevier BV, 2026)
Harmful algal blooms present severe ecological and public health challenges, creating an urgent need for sustainable remediation strategies. Here, we present a solar-powered electrochemical platform that generates hydrogen peroxide (H2O2) in-situ via the two-electron oxygen reduction reaction (2e– ORR), using a cobalt single-atom catalyst with Co–N4 sites anchored on crystalline carbon nanohorns (Co–N4Cl/CNH). Synchrotron X-ray absorption spectroscopy and electron microscopy confirm isolated Co–N4 active sites on the carbon support. The axial Cl coordination is known to modulate the oxidation state of Co-N4, suppressing O–O cleavage and promoting selective H2O2 generation. The Co–N4Cl/CNH catalyst achieves ∼80 % Faradaic efficiency for H2O2 production in a flow-cell under both alkaline and neutral conditions, enabling effective oxidation of cyanobacteria under environmentally relevant conditions. Compared to conventional chemical dosing of H2O2, this in situ electrochemical approach achieves faster and more complete cyanobacterial cell lysis within 6 h. To demonstrate real-world applicability, the Co–N4Cl/CNH cathode was integrated into an autonomous solar-powered floating platform that continuously generates H2O2 using only sunlight and ambient air, sustaining 24-hour operation with ∼9 h of daily solar charging and requiring no external power or chemical additives. Overall, this work showcases a unique integration of advanced single-atom catalysis with renewable energy and autonomous operation, bridging fundamental catalysis with practical environmental applications for sustainable harmful algal bloom remediation.